Return of the home run kid - Christopher, Matt.; Casale, Paul. (Boston : Little, Brown, 1992)
Sylvester Coddmyer III is having a dismal baseball season until he takes advice from a mysterious ex-ballplayer named Cheeko and starts to play more aggressively.
8 10 13 15 17 18 21 23 27 30 32 36
Keywords: Baseball -- Fiction